2012
DOI: 10.1038/ncomms2202
|View full text |Cite
|
Sign up to set email alerts
|

The metastasis-promoting S100A4 protein confers neuroprotection in brain injury

Abstract: Identification of novel pro-survival factors in the brain is paramount for developing neuroprotective therapies. The multifunctional S100 family proteins have important roles in many human diseases and are also upregulated by brain injury. However, S100 functions in the nervous system remain unclear. Here we show that the S100A4 protein, mostly studied in cancer, is overexpressed in the damaged human and rodent brain and released from stressed astrocytes. Genetic deletion of S100A4 exacerbates neuronal loss af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
117
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 61 publications
10
117
0
Order By: Relevance
“…These findings suggest that S100A4 may, in addition to its conventional role in carcinogenesis, also modulate posttraumatic events in the nervous system. Supporting this hypothesis, we recently found that S100A4 knockout increases neuronal loss after traumatic brain injury and identified two neurotrophic motifs in the S100A4 sequence (10). Synthetic peptides corresponding to these motifs (H3 and H6)…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…These findings suggest that S100A4 may, in addition to its conventional role in carcinogenesis, also modulate posttraumatic events in the nervous system. Supporting this hypothesis, we recently found that S100A4 knockout increases neuronal loss after traumatic brain injury and identified two neurotrophic motifs in the S100A4 sequence (10). Synthetic peptides corresponding to these motifs (H3 and H6)…”
Section: Introductionmentioning
confidence: 75%
“…We previously found that the S100A4 protein increases neuritogenesis and survival of primary neurons, and this effect is mediated by two motifs in the S100A4 sequence, H3 and H6 ( Figure 1A) (10). Because synthetic peptides corresponding to these motifs mimicked biological activities of S100A4 in animal models of brain trauma, we asked whether H3 and H6 also affect PNS regeneration after injury.…”
Section: Peptide Mimetics Of S100a4 Accelerated the Recovery After Scmentioning
confidence: 95%
See 3 more Smart Citations